Provokasi Aksi Massa dan Solusi Ijtihad Istislahi di Indonesia - Muhammad Aqsho Che Athoriq R; Kurniati K (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Mass protest provocation has become one of the most pressing challenges in maintaining social stability and public order in Indonesia. This phenomenon not only shapes public perception of demonstrations but also generates complex legal, social, and moral issues. Using an istislahi (public interest–oriented) framework, this study examines how the principle of maslahah can serve as a normative foundation for developing ethical and legal guidelines to prevent and mitigate provocation during demonstrations. Employing a library research method, this study explores relevant literature on mass action and contemporary Islamic legal thought to identify intersections between socio-political dynamics and maslahah-based legal constructions. The findings reveal that provocation within protests creates public harm (mafsadah) by triggering violence, damaging public property, and disrupting public order. The istislahi approach offers potential solutions through ethical protest guidelines, multidisciplinary collective ijtihad, and harmonization between Islamic legal values and public policy. Nevertheless, its implementation faces methodological, epistemic, institutional, and legitimacy challenges. This study highlights the urgency of integrating maslahah principles into public policy design to ensure that demonstrations remain safe, dignified, and free from provocation.